Tissue Inhibitor Of Matrix Metalloproteinase-1 Is Required for High-Fat Diet-Induced Glucose Intolerance and Hepatic Steatosis in Mice. - Even Fjære; Charlotte Andersen; Lene Secher Myrmel; Rasmus Koefoed Petersen; Jakob Bondo Hansen; Hanne Sørup Tastesen; Thomas Mandrup-Poulsen; Nils Brünner; Karsten Kristiansen; Lise Madsen; Maria Unni Rømer (PLoS ONE, 2015)
Plasma levels of tissue inhibitor of matrix metalloproteinase-1 (TIMP-1) are elevated in obesity and obesity-related disorders, such as steatosis, but the metabolic role of TIMP-1 is unclear. Here we investigated how the presence or absence of TIMP-1 affected the development of diet-induced glucose intolerance and hepatic steatosis using the Timp1 null mice.Timp1 knockout (TKO) and wild type (TWT) mice were fed chow, high-fat diet (HFD) or intermediate fat and sucrose diet (IFSD). We determined body weight, body composition, lipid content of the liver, energy intake, energy expenditure, oral glucose tolerance, as well as insulin tolerance. In addition, the histology of liver and adipose tissues was examined and expression of selected genes involved in lipid metabolism and inflammation in liver and adipose tissues was determined by RT-qPCR.TKO mice gained less weight and had lower energy efficiency than TWT mice when fed HFD, but not when fed chow or IFSD. Importantly, TKO mice were protected from development of HFD- as well as IFSD-induced glucose intolerance, hepatic steatosis, and altered expression of genes involved in hepatic lipid metabolism and inflammation.Collectively, our results indicate that TIMP-1 contributes to the development of diet-induced hepatic steatosis and glucose intolerance and may be a potential therapeutic target.